CLINICAL, PARACLINICAL CHARACTERISTICS AND COLONOSCOPIC FINDINGS IN PATIENTS WITH ANKYLOSING SPONDYLITIS IN THAI NGUYEN (Vietnam Journal of Community Medicine, 2026)
Objective: Description of colonoscopic lesion characteristics and related factors in patients with spondyloarthritis treated in Thai Nguyen.Subjects and methods: A cross-sectional descriptive study was conducted on 46 patients diagnosed with ankylosing spondylitis according to the 2009 ASAS criteria, from June 2024 to September 2025, at the Department of Rheumatology of Hospital A and Thai Nguyen National Hospital.Results: The locations of joint pain observed clinically were most commonly in the axial joints, while peripheral joints were less frequently affected and typically involved the lower limbs. In the study group, 10.9% of patients presented with gastrointestinal symptoms, among which digestive disorders and abdominal pain were the most common. Colonoscopy results showed colonic mucosal lesions in 21.7% of cases. The most frequent sites of endoscopic lesions were the ileocecal region and the rectum. Congestion and edema were the two most common endoscopic lesion types. The degree of mucosal damage was generally mild, accounting for 10.9% of cases. There was a significant correlation between age at disease onset and the presence of peripheral arthritis symptoms with HLA-B27 positivity, as well as between gastrointestinal symptoms and endoscopic colonic lesions (p < 0.05).Conclusion: Colonoscopy should be performed in patients with spondyloarthritis to detect early intestinal lesions, even in the absence of gastrointestinal symptoms, in order to facilitate early diagnosis and timely treatment.